2020
DOI: 10.1155/2020/8360936
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Growth Differentiation Factor-15 in Recurrence of Atrial Fibrillation after Catheter Ablation

Abstract: The mechanisms underlying the recurrence of atrial fibrillation (AF) after radiofrequency catheter ablation (RFCA) are not well concerned. The study sought to explore the association between growth differentiation factor-15 (GDF-15) and the incidence of recurrent events among AF patients after the ablation procedure. We prospectively included 150 consecutive AF patients who underwent RFCA. Clinical information about the patients was collected. Blood samples on the second morning of hospital admission and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 46 publications
(53 reference statements)
4
21
1
4
Order By: Relevance
“…The difference in these findings may be due to the differing baseline variables and conditions for patient participation in the two studies. Our research only excluded patients with AF who had moderate to severe mitral valve disease, while previous studies excluded patients with AF who had any degree of heart valve disease (30); however, we consider our findings more valid since they represent the condition of the vast majority of patients who attend hospital. Secondly, the duration of AF in our sample was longer than in previous research (30).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The difference in these findings may be due to the differing baseline variables and conditions for patient participation in the two studies. Our research only excluded patients with AF who had moderate to severe mitral valve disease, while previous studies excluded patients with AF who had any degree of heart valve disease (30); however, we consider our findings more valid since they represent the condition of the vast majority of patients who attend hospital. Secondly, the duration of AF in our sample was longer than in previous research (30).…”
Section: Discussionmentioning
confidence: 90%
“…Our research only excluded patients with AF who had moderate to severe mitral valve disease, while previous studies excluded patients with AF who had any degree of heart valve disease (30); however, we consider our findings more valid since they represent the condition of the vast majority of patients who attend hospital. Secondly, the duration of AF in our sample was longer than in previous research (30). This could be related to extensive atrial structural remodeling because an enhancement in AF's duration has been correlated with a greater extent of LA fibrosis (35).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In general, the eligible studies were published from 2011 to 2020, and their sample size ranged from 100 to 3,217 participants. Four studies reported the association between serum GDF-15 level and the risk of AF in the general population [7][8][9]24], 2 studies concentrated on patients who received coronary artery bypass graft [25,26], and 2 studies reported this association in patients with recurrent AF after catheter ablation [27,28]. The majority of the eligible studies were performed in Europe [7, 10, 24-27] (n=6), two studies were undertaken in China [8,28], and only one study was conducted in the United States [9].…”
Section: Study Characteristics and Quality Of The Eligible Studiesmentioning
confidence: 99%